The Historiography of Enlightenment Ideas in Central Asia - Umida Xolova (International Journal on Integrated Education, 2026)
This article examines the level of scholarly research on Enlightenment ideas in Central Asia from a historiographical perspective. It analyzes the contributions of domestic and foreign researchers to the study of the region's intellectual and educational heritage. The paper highlights the main directions, methodological approaches, and achievements in the study of Enlightenment thought, while also identifying existing research gaps and promising areas for future investigation. The findings contribute to a deeper understanding of the development of Enlightenment ideas and their role in the social, cultural, and educational transformation of Central Asia.